(untitled) (Multidisciplinary Journal of Science and Technology, 2024)
In this article, we have learned the theoretical knowledge of the relationships between family and neighborhoods, as well as some recommendations for further development of our relationships. In the upbringing of young people in the mahallas we need to use the method of our ancestors, to be based on our historical tradition and our national education. The most important element in the field of education is the universal human and national cultural values. This is the training of young people on the basis of the historical, national cultural heritage, the traditions of national education that have been formed over thousands of years.